Management of imported malaria in Europe - Askling, Helena H; Bruneel, Fabrice; Burchard, Gerd; Castelli, Francesco; Chiodini, Peter L; Grobusch, Martin P; Lopez-Vélez, Rogelio; Paul, Margaret; Petersen, Eskild; Popescu, Corneliu; Ramharter, Michael; Schlagenhauf, Patricia (Malaria journal, 2012)
In this position paper, the European Society for Clinical Microbiology and Infectious Diseases, Study Group on Clinical Parasitology, summarizes main issues regarding the management of imported malaria cases. Malaria is a rare diagnosis in Europe, but it is a medical emergency. A travel history is the key to suspecting malaria and is mandatory in patients with fever. There are no specific clinical signs or symptoms of malaria although fever is seen in almost all non-immune patients. Migrants from malaria endemic areas may have few symptoms. Malaria diagnostics should be performed immediately on suspicion of malaria and the gold- standard is microscopy of Giemsa-stained thick and thin blood films. A Rapid Diagnostic Test (RDT) may be used as an initial screening tool, but does not replace urgent microscopy which should be done in parallel. Delays in microscopy, however, should not lead to delayed initiation of appropriate treatment. Patients diagnosed with malaria should usually be hospitalized. If outpatient management is preferred, as is the practice in some European centres, patients must usually be followed closely (at least daily) until clinical and parasitological cure. Treatment of uncomplicated Plasmodium falciparum malaria is either with oral artemisinin combination therapy (ACT) or with the combination atovaquone/proguanil. Two forms of ACT are available in Europe: artemether/lumefantrine and dihydroartemisinin/piperaquine. ACT is also effective against Plasmodium vivax , Plasmodium ovale , Plasmodium malariae and Plasmodium knowlesi , but these species can be treated with chloroquine. Treatment of persistent liver forms in P. vivax and P. ovale with primaquine is indicated after excluding glucose 6 phosphate dehydrogenase deficiency. There are modified schedules and drug options for the treatment of malaria in special patient groups, such as children and pregnant women. The potential for drug interactions and the role of food in the absorption of anti-malarials are important considerations in the choice of treatment. Complicated malaria is treated with intravenous artesunate resulting in a much more rapid decrease in parasite density compared to quinine. Patients treated with intravenous artesunate should be closely monitored for haemolysis for four weeks after treatment. There is a concern in some countries about the lack of artesunate produced according to Good Manufacturing Practice (GMP).